Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0735-1097(00)01019-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitral regurgitation in hypertrophic obstructive cardiomyopathy: relationship to obstruction and relief with myectomy

Abstract: For patients with HOCM and MR not due to independent mitral valve disease, myectomy significantly reduced the degree of MR, without requirement for additional mitral valve surgery. In these patients the severity of MR was directly related to the magnitude of the LVOT gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(127 citation statements)
references
References 41 publications
2
106
2
6
Order By: Relevance
“…Such MR, however, is usually associated with an intrinsically normal mitral valve and the severity of the MR is directly related to the LVOT gradient (1). The association of MVP, with or without chordal rupture, has been reported to complicate HCM (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such MR, however, is usually associated with an intrinsically normal mitral valve and the severity of the MR is directly related to the LVOT gradient (1). The association of MVP, with or without chordal rupture, has been reported to complicate HCM (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the association of MVP and HCM "may reflect the coexistence of two separate but primary disease entities." Yu et al (3), from the Toronto General Hospital (Toronto, Ontario), reviewed their operative experience with HOCM and reported that 11 of 104 patients (11%) had independent mitral valve disease. Of these, five had more than moderate MVP and one patient had ruptured chordae.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that after septal myectomy, all of the patients experienced a significant reduction in MR degree: no MR in 80%, mild in 19%, moderate in 1%. 142 The main complications were atrioventricular nodal block, ventricular septal defect and aortic regurgitation. 137 This method is now associated with a less than 1% mortality risk 143 , including a decrease in the LVOT gradient from 78 mmHg to 11 mmHg and an improvement in 98% of the patients concerning the NYHA class (I, II).…”
Section: Septal Myectomymentioning
confidence: 99%
“…Left ventricular outflow tract (LVOT) obstruction is an important complication of hypertrophic cardiomyopathy, related to symptoms, functional limitations, and prognoses of the patients [1][2][3], and various types of medical and surgical interventions are performed to reduce the pressure gradient in LVOT [4][5][6][7][8][9][10][11][12][13][14][15]. The degree of dynamic obstruction seen in patients with hypertrophic obstructive cardiomyopathy (HOCM) can vary markedly by the physiological changes in preload, contractility, and afterload [16][17][18].…”
Section: Introductionmentioning
confidence: 99%